Perdagangan Tenaga Kerja Di Indonesia: Analisis Patologi Sosial Dan Perlindungan Hukum - Ellie Andini; Tiara Okta Yanti; Reza Seby Alfikri; Anjar Rusadi; Helda Rahmasari; Wevy Efticha Sary (GLOBAL SCIENTS PUBLISHER, 2025)
This study analyzes the trafficking of Indonesian Migrant Workers (TKI) and Female Migrant Workers (TKW) abroad as a social pathology and the effectiveness of legal protection. Despite regulations such as Law No. 21 of 2007 and Law No. 18 of 2017, illegal agents, non-procedural departures, exploitation, and limited victim access to legal protection remain. This normative study uses literature and legal document analysis to identify gaps between regulation and implementation in the socio-economic context of migrant workers. Findings show TKI atau TKW trafficking is a systemic social issue influenced by poverty, low education, and limited employment alternatives. Effective legal protection requires strengthened regulations, agent supervision, public education, capacity building, international intervention, and socio-economic rehabilitation for victims. The study provides policy recommendations to enhance migrant worker protection and sustainably prevent human trafficking.